Technology Education Transformation of Education Technology 5.0 through 360-Based Digital Modules for Tourism Vocational Schools in Bandung City: English - Suwandi Andreas; Cica Yulia; Ade Gaffar Abdullah; Rini Andari; Nadhia Maesari (CV. Get Press Indonesia, 2026)
The concept of Digital Education 5.0 in tourism education emphasizes the integration of scientific and technological innovations to create an effective, interactive, and future-oriented learning environment. This study aims to examine the role of Digital Education 5.0 transformation through the incorporation of science and technology innovations, particularly in Tourism Vocational Schools. A qualitative approach was employed using literature review, interviews, and observation methods. Data were collected from relevant academic sources, interview results, and field observations to develop a comprehensive understanding of Digital Education 5.0 and its application in tourism vocational education. The participants in this study consisted of 100 students from Tourism Vocational Schools. Data analysis was conducted using descriptive and verification techniques to systematically interpret the findings. The results indicate that the implementation of Digital Education 5.0 provides significant opportunities to improve teaching and learning processes. The integration of advanced technologies such as artificial intelligence, virtual reality, and the Internet of Things supports the development of a technology-based learning ecosystem that enhances students’ motivation, engagement, and participation. Furthermore, innovative pedagogical approaches, including flipped classroom, blended learning, and personalized learning, enable educators to deliver learning materials in more flexible and engaging ways while fostering effective collaboration between teachers and students. However, the transition toward Digital Education 5.0 also presents challenges related to technological readiness and the need for continuous capacity building for both teachers and students.